Frequency and risk factors of gastric and duodenal ulcers or erosions in children: a prospective 1-month European multicenter study - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2010)
There are no solid figures of the frequency of ulcer disease during childhood in Europe. We assessed its frequency and analyzed known risk factors. Patients and methods Ulcers, erosions, indications, and risk factors were recorded in all children undergoing an upper gastrointestinal endoscopy in a prospective study carried out during 1-month simultaneously in 19 centers among 14 European countries. Results Ulcers and/or erosions were observed in 56 out of 694 children. Children with ulcers/erosions were significantly older than those without lesions (10.3 +/- 5.5 vs. 8.1 +/- 5.7 years, P = 0.002). Helicobacter pylori infection was present in 15 of 56 children (27%) where NSAIDs were used in eight, steroids in five, immune-suppressive drugs in five, antibiotics in six, antacids in one, H2-blockers in six and proton pump inhibitors in eight children (more than one risk factor was detected in 32 of 56 children). No risk factors were observed in 24 of 56 children (43%). The main indications for endoscopy were epigastric or abdominal pain (24%) and suspicion of gastroesophageal reflux disease (15%). Similarly, epigastric tenderness, hematemesis, melena, and weight stagnation were significantly associated with ulcers/erosions, whereas sex, H. pylori infection, socioeconomic and lifestyle factors were equally distributed. Conclusion Although limited by the short-time duration and the heterogeneity of the patients included throughout the 19 centers, our study shows a frequency of 8.1% of ulcers and/or erosions in children, occurring mainly in the second decade of life. H. pylori infection and gastrotoxic medications were less frequently implicated than expected. Eur J Gastroenterol Hepatol 22: 1174-1181 (C) 2010 Wolters Kluwer Health | Lippincott Williams & Wilkins.
Keywords: child; erosion; Helicobacter pylori; ulcer; HELICOBACTER-PYLORI; PEPTIC-ULCER; DISEASE; COMMON